Spatial Assessment for Coal Fire Power Plant: A Case Study of Songkla Province - Takamol, Supakorn; Chompunth, Chutarat; Poboon, Chamlong (Burapha Science Journal, 2026)
The southern of Thailand has faced the risk of electricity shortage because of the continuously high demand. Songkhla province has the most electricity consumption, thus the government should develop the power plant in Songkla. This research aimed to present a suitable area and suggested approaches to manage the construction of a coal fire power plant in Songkla. This research is a qualitative research based on the Regional Environmental Assessment (REA). The concerned criteria were environmental, social, economic, and technology. The Analytic Hierarchy Process (AHP) was employed as the methodological tool for weighing the criteria, and data were collected through in-depth interviews with key informants for the public hearing. The result showed that Tambon Sabayoi, Amphoe Sabayoi, is a suitable area for power plant construction because it meets with most of the investigated criteria. However, local people still worried about the pollution and loss of domain. To be successful, the government must increase the public confidence level, and the public should have sufficient knowledge and understanding about the project, be allowed to participate in the decision-making process. It should be done in order to resolve the problem of the project